Pengaruh Penerapan Good Corporate Covernance Terhadap Kinerja Perusahaan pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2019-2022 - Rosita Situmorang; Ardin Dolok Saribu; Audrey M Siahaan (Masyarakat Ekonomi Syariah Bogor, 2024)
The objectives of this study are as follows: 1) To determine the effect of an independent board of commissioners on company performance in the company. 2) To determine the effect of institutional ownership on company performance in the company. 3) To determine the effect of managerial ownership on company performance in the company. 4) To determine the effect of the audit committee on company performance in the company. The sample of this study was 10 companies. The results of the study are 1) An independent board of commissioners has a positive effect on company performance in the company. 2) Institutional ownership has a positive effect on company performance in the company. 3) Managerial ownership has a positive and significant effect on company performance in the company. 4) The audit committee does not have a significant effect on company performance in the company.